Bayesian inference in measurement error models for replicated data. Issue 1 (15th November 2012) - de, Mário; Bolfarine, Heleno; Galea, M.
<x xml:space="preserve">Abstract</x> This paper deals with Bayesian inference in measurement error models with unknown error covariances. Our formulation covers heteroscedastic and homoscedastic models for replicated data. Both equation‐error and no‐equation‐error models are included in our proposal. Resorting to data augmentation, we present a simulation‐based framework using the Gibbs sampler. Model selection is also briefly discussed. Results from a simulation study are reported. We work out an illustrative example with a real data set on measurements of mineral element contents in pottery samples. Copyright © 2012 John Wiley & Sons, Ltd.